A Perspective of Theory Technology-To-Performance Chain (TPC): Accounting Information Systems, Internal Control and Work Motivation on Employee Performance - Fuadi, Agus; Dian Sulistyorini Wulandari; Verentia Amranani Putri (Indonesian Journal of Economic & Management Sciences, 2024)
The advancement of technology is a reflection of the contemporary era, continually evolving to address the changing needs of humanity. Beyond the widespread demand for accounting information systems, it is crucial to recognize the substantial influence that internal control and work motivation wield over employee performance. This research endeavors to examine the impact of accounting information systems, internal control, and work motivation on the performance of PT Arfia Megah's employees. The study employs a saturated sampling method, encompassing the entire population of 40 employees at PT Arfia Megah. The independent variables under scrutiny include accounting information systems, internal controls, and work motivation, while employee performance serves as the dependent variable. Utilizing a quantitative approach, primary data is collected through a questionnaire, and the analysis is conducted using the multiple regression method. The findings affirm a positive correlation between accounting information systems, internal control, work motivation, and enhanced employee performance